Mídia e educação na cibercultura: uma pesquisa sobre a escola e o desenvolvimento de competências midiáticas - Sternberg, Melina Adissi (2018)
This research is aimed at understanding the development of media skills in schools in the context of cybercultural dromocracy. The primary objective is to understand these skills and their links with the social, economic and media context of the school, as well as the perspective of valuing technology in this environment. The corpus of the research will consist of interviews with pedagogical coordinators of the Mater Dei School, a private teaching institution in the city of São Paulo. The school provides digital media for educational purposes as part of the execution of its educational policy project. Intended for the regular activities of all curricular components, digital media are intrinsically linked to students' school routine. In these cases, the development of media skills is at stake, and that’s the central focus of the research. This concept is understood as the sum of technical, practical and cognitive skills that covers both the use of the media and the critical understanding of macrossocial and mediatic processes. As a consequence of technological development, the social, cultural, economic and/or political contexts of life were eventually mediatized, a scenario in which the media permeate the development of contemporary society. In the same context, new models of construction and mediation of knowledge emerge, prompted by the imperative of cyberculture dromocracy in this mediatized capitalist structure. In this scenario, which justifies the need for an in-depth investigation, the research problem concerns how and to what extent the institution appropriates the discourse of competence and/or dromocracy in order to determine the development of media skills in the school system. As a methodological strategy, the interviews with educational managers at the Mater Dei School, as well as the mapping of the characteristics of the school system studied, are based on the following hypothesis: a school has learning objectives focused on the development of media skills, incorporated into the curriculum of pedagogical coordination and teachers, as a consequence of demands outside the school, such as the need to train students able to deal with digital technologies